Acute onset sleep apnea with severe transient hyperglycemia in young adult: the diagnostic dilemma and management controversy - Mishra, Brajesh; Mishra, Bhawesh (International Journal of Research in Medical Sciences, 2017)
Sleep disordered breathing and obstructive sleep apnea are frequently associated with hyperglycemic disorders. The common pathophysiological factors that link these disorders have been a matter of debate and current research. Abdominal adiposity and high body mass index are considered to predispose individuals to early onset of type 2 diabetes and related metabolic disorders. A young adult presenting with symptoms of obstructive sleep apnea often poses a diagnostic challenge for clinicians especially when multiple risk factors coexist. It is essential to establish the exact diagnosis so that specific treatment can be initiated. The role of a non-aggressive approach in management of severe hyperglycemic conditions has been doubted. We report a case of a 33 year old man presenting to the respiratory outdoor clinic for recent onset loud snoring and increased daytime sleepiness. Routine biochemistry reports revealed hyperlipidemia and severe hyperglycemia. The patient was ambulatory and stable throughout. The subsequent investigations identified multiple stressors and the possibility of a single cause was analysed. A rapid glycemic control and amelioration of symptoms were observed based on consistent monitoring and a conservative clinical approach. The key findings and relevant review of literature are discussed in this article.